Organic Rankine Cycle (ORC) as waste heat recovery system for micro-cogeneration: a preliminary study - Saadon, Syamimi (IOP Publishing, 2021)
Although the energy consumption pattern has been optimized, the main problem facing by energy revolution is the low conversion efficiency of renewable energy and waste heat. Among the utilization technologies of these waste heat, organic Rankine cycle (ORC), which has characteristics of simple structure and high efficiency is chosen as the potential candidate to overcome this situation. However, ORC is facing several limitations including having low turbine performance leading to low power production. Additionally, the design of ORC and the heat recovery system should be improved to reduce the investment cost. One of the ways to increase the performance of this ORC is to design ORC waste heat recovery system for cogeneration. Thus, this study will be focused on to identify the effect of different heat exchanger positions to the ORC thermal performance and to investigate the effect of integrating ORC for cogeneration. In order to achieve this, identification of the suitable heat exchanger for ORC will be performed by modelling and simulation to predict the effect of the new design to the ORC thermal performance. Then, the improved novel ORC design will be integrated to a cogeneration system to simulate the power produced by the combined system.